Kopi sebagai Pangan Fungsional: Aktivitas Biologis, Manfaat Kesehatan dan Risiko Toksisitas - Destirana, Shalwa; Rahma, Rifa Nisrina; Sena, Muhammad Ibnu; Khotimah, Fathia Husnul; Primasari, Alina (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
Coffee is one of the world's most popular beverages and is renowned for its health benefits derived from its bioactive compounds, such as caffeine, chlorogenic acid, melanoidins, cafestol and kahweol. This research aims to assess the potential functional properties of coffee based on the latest scientific literature. Seventy-three scientific articles were systematically reviewed to identify coffee’s diverse biological activities its diverse biological activities, including antioxidant, anti-inflammatory, antimicrobial, anticancer, anti-obesity, anti-diabetic, hepatoprotective, and cognitive-enhancing effects. Furthermore, compounds in coffee have shown potential as prebiotics and anti-aging agents. However, coffee consumption carries toxic risks associated with excessive caffeine intake, ochratoxin A, and 5-hydroxymethylfurfural (5-HMF). Therefore, understanding the correct consumption dosage and safe processing methods is crucial. This review concludes that coffee possesses significant potential as a functional food that supports overall public health and warrants further development in the food and health sectors.Keywords – Antioxidants, Coffee, Functional Foods, Bioactive Compounds, Toxicity.